Performance Assessment of Concrete Structure Urea Fertilizer Dust Scrubber - Sumargo Sumargo; Zainudin Zainudin (Eduvest - Journal of Universal Studies, 2025)
The concrete dust scrubber building is a crucial treatment unit in a urea fertilizer plant, responsible for processing urea dust emissions. Given Indonesia's location in the Pacific Ring of Fire, ensuring the building’s structural integrity against seismic influences is essential. Regular structural evaluations using Destructive Testing (DT) and Non-Destructive Testing (NDT) help assess concrete strength, reinforcement conditions, and environmental effects on corrosion. Structural performance analysis was conducted using Robot Structural Analysis Professional software. Due to safety concerns over urea dust emission leakage, core drilling (DT) was not performed. Instead, concrete quality was assessed using the Hammer Test and Ultrasonic Pulse Velocity (UPV), yielding a compressive strength of 24.4 MPa. Reinforcement steel was evaluated through NDT methods, including carbonation, chloride, pH, and Half-Cell Potential (CANIN) testing, to assess environmental radiation effects. Steel Hardness Testing showed an average yield strength of 398 MPa, with a minimum of 396 MPa. The results indicated a 24 MPa reduction in steel quality due to environmental radiation. Structural performance was analyzed using ASCE 41-17 standards through Tier 1, Tier 2, and Tier 3 evaluations. The results demonstrated that the concrete dust scrubber building meets the stiffness, strength, and deformability criteria of SNI 1726:2019 for Special Moment Resisting Frame (SRPMK) systems. This confirms the building’s structural viability for continued operation in the urea fertilizer production process.